Effect of immersion in chemical solution on the mechanical & physical properties for composite material reinforced by Nano alumina Particles - Abd AL-Hussien, Huda .J. (Iraqi Journal of Science, 2023)
In this research Epoxy resin was reinforced by nano alumina (AL2O3) particles in grain size(25-30 nm) with two weight ratios (2,4)% then compared with pure Epoxy. Four mechanical tests were performed on these materials include Hardness, flexural, impact & compression strengths before and after immersion in tap water and chemical solutions (CH3COOH) acid, (KOH) base at (0.5N) ,The diffusivity coefficients of all prepared samples were calculate after immersion in water and chemical solutions mentioned above , the results were showed that the Flexural, Impact & Hardness increase after addition the ceramic particles (AL2O3) while the immersion process results showed illustrated different values from sample to other.